The Latin Language : Manual for Independent Work for the First-Year Students of the Pharmaceutical Faculties with the English Medium of Instruction, Speciality 226 “Pharmacy, Industrial Pharmacy” - Kulichenko, A. K.; Titiyevska, T. V.; Куліченко, Алла Костянтинівна; Тітієвська, Тетяна Василівна (Запорізький державний медичний університет, 2022)
The manual is made up for the first-year students of the pharmaceutical faculties with the English medium of instruction, speciality 226 “Pharmacy, Industrial Pharmacy”. The manual contains specialized design-structure tasks for independent work. The purpose of the manual is to revise the material learnt during Latin classes and to prepare for assessment and credit in the Latin language.